Viral Hepatitis in pregnancy - Victor N. Chilaka (16936929) (2020)
The global prevalence of viral hepatitis is very high and seems to be rising over the years. The infection can profoundly affect pregnant women causing significant maternal and perinatal morbidity and mortality with some strains much worse than others.Hepatitis A (HAV) and E (HEV) which are transmitted mainly through the faecal-oral route present as acute hepatitis during pregnancy and are responsible for most local epidemic outbreaks. HAV infection remains self-limiting during pregnancy, while HEV has a higher prevalence and causes significant morbidity. It is also associated with a very high maternal mortality rate (20 %) and requires special attention in endemic areas. HEV vaccines do exist, but the WHO has yet to approve them for general use. Hepatitis B is the most prevalent form and is part of the ante-natal screening program. The presence of HBeAg is associated with high viral loads and infectivity. Antiviral therapy, preferably tenofovir (TDF), is recommended for mothers with viral load ≥ 200,000 IU/mL2), with the neonates receiving both active and passive immunisations. Hepatitis C and D are usually found as chronic infections in the pregnant and non-pregnant populations. Screening for hepatitis C during pregnancy and its subsequent management is still unsettled, but the introduction of direct-acting antiviral (DAA) drugs will change the picture if their safety is established in pregnancy. HDV is an incomplete virus linked to HBV and cannot establish an infection on its own. Controlling HBV is paramount to controlling HDV. HEV is quite prevalent and looked upon as hepatotropic. It seems to be quite prevalent in some blood donor populations and has a high co-infection rate with HCV. It has a high Mother-to-Child-Transmission (MTCT) but causes little or no illness in infected infants, and antenatal screening is not justified.This review summarises the prevalence, clinical picture, maternal, perinatal effects, and the management and prevention of hepatitis A, B, C, D, E and G viral infections during pregnancy. Other Information Published in: European Journal of Obstetrics & Gynecology and Reproductive Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ejogrb.2020.11.052